Toward a Christology for Korean Immigrants in North America: A Critical Interaction of James Cone and J.Y. Lee - Heo, Chun-Hoi (Toronto journal of theology, 2004)
The catalyst for this essay is my own experience as a first-generation Korean Christian immigrant in the North American context. Although no one "experience" can become theologically normative for the Christian community, the experiences and voices of the oppressed and the marginalized have too long been ignored, or interpreted from the perspective of those who are culturally and politically dominant.! When we speak of "experience" as a factor in theological method, we acknowledge cultural, racial or gender specificities, and also we recognize the differences between the rich and the poor, the dominator and the dominated, those at the "center" and those at the margins. Experiences of the poor, oppressed and marginalized will provide hermeneutical insights, which may not only contribute to developing theologies for ethnic minorities in North America in particular, but also open windows for overcoming the limits of traditional theology.